2023
DOI: 10.1371/journal.pone.0282014
|View full text |Cite
|
Sign up to set email alerts
|

Habitats generated by the restoration of coal mining subsidence land differentially alter the content and composition of soil organic carbon

Abstract: The content and composition of soil organic carbon (SOC) can characterize soil carbon storage capacity, which varies significantly between habitats. Ecological restoration in coal mining subsidence land forms a variety of habitats, which are ideal to study the effects of habitats on SOC storage capacity. Based on the analysis of the content and composition of SOC in three habitats (farmland, wetland and lakeside grassland) generated by different restoration time of the farmland which was destroyed by coal mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Soil SUC can increase the soluble nutrients in soil, and its activity is closely related to the transformation, decomposition, and accumulation of SOM [47]. In this study, soil URE and SUC activities showed highly significant positive correlations with SOM and soil AN (Figure 5); this was attributed to the loss of SOM in coal mining subsidence areas with high underground water levels, which is conducive to soil denitrification [48]. The content of soil AN was reduced, resulting in a reduction in substrates for enzymatic reactions, and the activities of SUC and URE were reduced accordingly.…”
Section: Response Of Soil Enzyme Activity To Soil Physicochemical Pro...mentioning
confidence: 56%
“…Soil SUC can increase the soluble nutrients in soil, and its activity is closely related to the transformation, decomposition, and accumulation of SOM [47]. In this study, soil URE and SUC activities showed highly significant positive correlations with SOM and soil AN (Figure 5); this was attributed to the loss of SOM in coal mining subsidence areas with high underground water levels, which is conducive to soil denitrification [48]. The content of soil AN was reduced, resulting in a reduction in substrates for enzymatic reactions, and the activities of SUC and URE were reduced accordingly.…”
Section: Response Of Soil Enzyme Activity To Soil Physicochemical Pro...mentioning
confidence: 56%
“…The "Five Small Projects" are supported by special funds for agricultural water conservancy, aiming to continuously build water conservancy facilities to expand the storage area of small-and medium-sized lakes and the water flow of main rivers (Figure 12b) [76]. On the other hand, the policy of returning farmland to forest/grassland is intended to achieve the self-repair of the natural wetland ecosystems by limiting human intervention in the natural environment and utilizing highquality water sources [77]. Therefore, with the support of these policies, human agricultural activities in some areas have gradually reduced, and the natural wetland coverage has started to slowly rebound, as observed in the Hulunbeier and Daxinganling regions from 2005 to 2010.…”
Section: Spatiotemporal Variation Of Natural Wetlandsmentioning
confidence: 99%